2000
DOI: 10.1046/j.1444-2906.2000.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual levels of phosphatidylcholine hydroperoxide in plasma, red blood cell, and livers of aromatic fish

Abstract: SUMMARY: Levels of phosphatidylcholine hydroperoxide (PC‐OOH) in plasma, red blood cell (RBC), and livers of cultured and commercially available marine and freshwater fish were determined quantitatively by normal phase high‐performance liquid chromatography (HPLC) equipped with a post‐column detection system, using diphenyl‐1‐pyrenyl phosphine as a fluorescence reagent. The levels of plasma PC‐OOH in non‐aromatic fish, including yellowtail, amberjack, the Japanese flounder, sea bream, and rainbow trout ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“… 23 Recently, a group with one of the authors found that unusual amounts of lipid hydroperoxides accumulated in the tissues of aromatic fish including sweet smelt. 24 They postulated that certain polyunsaturated fatty acids could be the precursors of the hydroperoxides in aromatic fish such as sweet smelt. Because most consumers prefer the sweet smelt with an intense characteristic aroma, the qualitative and quantitative characteristic of polyunsaturated fatty acids might be the key indices of fish quality in terms of aroma.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Recently, a group with one of the authors found that unusual amounts of lipid hydroperoxides accumulated in the tissues of aromatic fish including sweet smelt. 24 They postulated that certain polyunsaturated fatty acids could be the precursors of the hydroperoxides in aromatic fish such as sweet smelt. Because most consumers prefer the sweet smelt with an intense characteristic aroma, the qualitative and quantitative characteristic of polyunsaturated fatty acids might be the key indices of fish quality in terms of aroma.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction progresses in different types of solvents (14). A few applications of this system have already been reported for the analyses of hydroperoxides of TAG, cholesterol, cholesterol esters, and phospholipids in biological systems (15)(16)(17)(18)(19)(20). This method has also been applied to analyze the distributions of…”
mentioning
confidence: 95%
“…As primary products of lipid peroxidation in fish tissues, lipid hydroperoxides are usually produced by inherent lipoxygenase 1,2 and further decompose to low molecular volatile compounds, including aldehydes, alcohols and ketones, which are involved in the development of aromas in the biological tissues of fish 3–5 . In previous studies, we found that the levels of hydroperoxides in the plasma, red blood cell and livers of aromatic fish, including sweet smelt, shishamo smelt, the Japanese smelt and rainbow smelt, were significantly higher than those of non‐aromatic fish, including yellowtail, amberjack, rainbow trout, the Japanese flounder and red sea bream 6 . Certain aromatic fish such as the Australian grayling, whitefish, rainbow smelt and sweet smelt contained high levels of ( E )‐2‐nonenal ( E , Z )‐2,6‐nonadienal and 3,6‐nonadien‐1‐ol in their tissues 7–11 .…”
Section: Introductionmentioning
confidence: 75%
“…The column oven temperature was held initially at 150°C for 2 min, then programmed to 180°C at a rate of 5°C/min, from 180°C to 240°C at the rate of 1.2°C/min, and finally held at 240°C for 35 min. Helium was used as carrier gas under a column inlet pressure of 140 kPa and a split ratio of 1 : 20 6 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation